Identification of a Specific Assembly of the G Protein Golf as a Critical and Regulated Module of Dopamine and Adenosine-Activated cAMP Pathways in the Striatum - Hervé, Denis (Frontiers in Neuroanatomy, 2011)
In the principal neurons of striatum (medium spiny neurons, MSNs), cAMP pathway is primarily activated through the stimulation of dopamine D1 and adenosine A2A receptors, these receptors being mainly expressed in striatonigral and striatopallidal MSNs, respectively. Since cAMP signaling pathway could be altered in various physiological and pathological situations, including drug addiction and Parkinson’s disease, it is of crucial importance to identify the molecular components involved in the activation of this pathway. In MSNs, cAMP pathway activation is not dependent on the classical Gs GTP-binding protein but requires a specific G protein subunit heterotrimer containing Galpha-olf/beta2/gamma7 in particular association with adenylate cyclase type 5. This assembly forms an authentic functional signaling unit since loss of one of its members leads to defects of cAMP pathway activation in response to D1 or A2A receptor stimulation, inducing dramatic impairments of behavioral responses dependent on these receptors. Interestingly, D1 receptor-dependent cAMP signaling is modulated by the neuronal levels of Galpha-olf, indicating that Galpha-olf represents the rate-limiting step in this signaling cascade and could constitute a critical element for regulation of D1 receptor responses. In both Parkinsonian patients and several animal models of Parkinson’s disease, the lesion of dopamine neurons produces a prolonged elevation of Galpha-olf levels. This observation gives an explanation for the cAMP pathway hypersensitivity to D1 stimulation, occurring despite an unaltered D1 receptor density. In conclusion, alterations in the highly specialized assembly of Galpha-olf/beta2/gamma7 subunits can happen in pathological conditions, such as Parkinson’s disease, and it could have important functional consequences in relation to changes in D1 receptor signaling in the striatum.